Developing A New Sense Amplifier By Applying The Method Of The Dissipation Power Reduction For Sram - Momjyan, A. M. («Պոլիտեխնիկ» տպ.)
A voltage latch sense amplifier by applying the power consumption reduction method is introduced. The presented sense amplifier is compared with the classical voltage latch-type sense amplifier and an amplifier with a leakage control (LECTOR) technique is applied. The designs are carried out by 14 nm FinFET technology. The results of simulations show that in the case of the proposed design, the power dissipation and propagation delay is improved. Simulation is performed for typical-typical (tt), slow-slow (ss), and fast-fast (ff), process voltage temperature (PVT) corners. Ներկայացված է նոր լաչ ընթերցող ուժեղարար՝ հզորության նվազեցման միջոցի կիրառմամբ։ Զգայուն ուժեղարարը համեմատվել է դասական լարման լաչ և կորստի հոսանքի կառավարման (ԼԵԿՏՈՐ) մեթոդի կիրառմամբ ուժեղարարի հետ։ Նախագծումը կատարվել է 14նմ FinFET տեխնոլոգիայով։ Նմանակման արդյունքները ցույց են տալիս, որ առաջարկված նախագծի դեպքում ունենք բարելավված հզորության ցրում և հապաղում։ Նմանակումները կատարվել են տիպային-տիպային (tt), դանդաղդանդաղ, արագարագ գործընթաց, լարում, ջերմաստիճան (ԳԼՋ) եզրային պարամետրերով։ Представлена новая схема чувствительного усилителя типа латч с применением метода уменьшения энергопотребления. Проведено сравнение предложенного чувствительного усилителя с классическим усилителем типа латч и с усилителем, к которому применена техника контроля утечного тока (ЛЕКТОР). Схема разработана по технологии FinFET 14 нм. Результаты симуляции схемы показывают, что в случае предложенной схемы были улучшены рассеиваемая мощность и задержка распространения. Выполнено моделирование с применением следующих граничных значений по напряжению и температуре: типичное-типичное, медленное-медленное и быстрое-быстрое.
Keywords: Microelectronics